Trichinella nativa in red foxes (Vulpes vulpes) of Germany and Poland: possible different origins - Chmurzynska, E.; Rozycki, M.; Bilska-Zajac, E.; Nöckler, K.; Mayer-Scholl, A.; Pozio, E.; Cencek, T.; Karamon, J. (Veterinary Parasitology, 2013)
In Germany and Poland, the high population density of the red fox (Vulpes vulpes) is considered a public health risk since this wild canid is one of the main reservoirs of Trichinella spp. In 2010 in Poland, a program to monitor the prevalence of Trichinella spp. in the red fox population was launched. After two years, Trichinella spp. larvae were detected in 44 (2.7%) out of 1634 foxes tested. In Germany in the period 2002-2011, Trichinella spp. larvae were in 27 foxes. The Trichinella species detected were: T. spiralis in 15 foxes from Germany (one co-infection with Trichinella britovi and one with Trichinella pseudospiralis) and in 9 foxes from Poland; T. britovi in 8 and 32 foxes from Germany and Poland, respectively; and T. pseudospiralis in 1 fox from Germany. The arctic species Trichinella nativa was detected in 3 foxes from Germany (one co-infection with Trichinella spiralis) and in 1 fox from Poland. The detection of T. nativa outside its known distribution area opens new questions on the ability of this Trichinella species to colonize temperate regions